Barriers and Facilitators to Seeking Mental Health Care Among First Responders: "Removing the Darkness". (January 2020) - Jones, Sara; Agud, Katherine; McSweeney, Jean
BACKGROUND: First responders (FRs) are at significant risk for developing mental health (MH) problems due to the nature, frequency, and intensity of duty-related traumatic exposure. However, their culture strongly esteems strength and self-reliance, which often inhibits them from seeking MH care.AIMS: This study explored factors that influenced FRs' perceptions of MH problems and engagement in MH services.METHODS: A community-based approach and individual ethnographic qualitative interviews were used. Recruitment of a convenience sample of firefighters and emergency medical technicians/paramedics from across Arkansas was facilitated by our community partners. Interviews were analyzed using content analysis and constant comparison.RESULTS: Analysis generated three broad factors that influenced FRs' perception of MH problems and engagement in MH services: (a) Knowledge, (b) Barriers to help-seeking, and (c) Facilitators to help-seeking. Knowledge was an overarching factor that encompassed barriers and facilitators: A lack of knowledge was a barrier to help-seeking but increased knowledge served as a facilitator. Barriers included five subthemes: Can't show weakness, Fear of confidentiality breech, Therapist: negative experience, Lack of access and availability, and Family burden. Facilitators included five subthemes: Realizing "I'm not alone, " Buy-in, Therapist: positive experience, Problems got too bad, and Recommendations.CONCLUSIONS: Findings provide unique perspectives from FRs about how to best address their MH needs. First responders, as well as mental health care providers, need a more thorough understanding of these issues in order to mitigate barriers and facilitate help-seeking. As advocates, educators, and health care providers, psychiatric nurses are well-positioned to care for this at-risk population.